2020
DOI: 10.1002/pros.24059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiation dose on recurrence in high‐risk prostate cancer patients

Abstract: Background Dose escalated radiation therapy (RT) combined with long‐term androgen deprivation therapy (ADT) is a standard of care option for men with high‐risk and locally advanced prostate cancer (PCa). However, the optimal dose of escalated RT and ADT is not known. Here we assessed the impact of radiation dose and length of ADT on biochemical recurrence in a multi‐institutional cohort stratified by the Cambridge prognostic group (CPG). We hypothesized that radiation dose and length of ADT would impact outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…( 19 ) also found that nearly all recurrences were within the extent of the primary index tumor. These findings indicate that the radiotherapy of primary prostate cancer could be improved by dose escalation ( 20 ). Modern dose painting techniques may deliver increased dose selectively to the radio-persisting intra-prostatic lesion without increasing the dose to the OARs ( 21 ).…”
Section: Discussionmentioning
confidence: 89%
“…( 19 ) also found that nearly all recurrences were within the extent of the primary index tumor. These findings indicate that the radiotherapy of primary prostate cancer could be improved by dose escalation ( 20 ). Modern dose painting techniques may deliver increased dose selectively to the radio-persisting intra-prostatic lesion without increasing the dose to the OARs ( 21 ).…”
Section: Discussionmentioning
confidence: 89%